A method of intensively cooling and granulating blast furnace slag
By using gas-solid two-phase flow mixing to enhance the crushing and granulation of blast furnace slag, a cold core and hot slag structure is formed, which solves the problems of insufficient waste heat utilization and environmental pollution in blast furnace slag treatment, realizes the efficient preparation of high-performance cement raw materials, and enhances the added value of blast furnace slag utilization.
Patent Information
- Application Number
- CN202311045328.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-18
- Publication Date
- 2025-11-21
- Estimated Expiration
- 2043-08-18
AI Technical Summary
Existing blast furnace slag treatment methods suffer from problems such as high water consumption, unutilized waste heat, serious environmental pollution, and low added value. Furthermore, the air quenching method requires large equipment and consumes a lot of energy, which limits the subsequent utilization of slag products.
A gas-solid two-phase flow mixing and enhanced crushing method is adopted. A cold core hot slag structure is formed by high-pressure airflow and solid cold material injection, which synergistically cools granulated blast furnace slag, improves the bead formation rate and glass content of amorphous slag beads, and prepares high-efficiency cement raw materials.
It significantly improves the glass content and cement performance of amorphous blast furnace slag beads, increases cement substitution, reduces production costs and environmental pollution, and enhances the added value of blast furnace slag utilization.
Smart Images

Figure CN117025863B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of blast furnace slag resource utilization and waste heat efficient utilization technology, specifically relating to a method for enhanced cooling and granulation of blast furnace slag. Background Technology
[0002] Blast furnace slag is a large-volume solid waste generated during the blast furnace ironmaking process. It is produced in large quantities and has a high waste heat value. Long-term untreated stockpiling will inevitably lead to loss of activity, increasing the difficulty of reprocessing and causing waste to the soil and pollution to the atmosphere. my country is a major steel producer, ranking among the world's top producers of pig iron annually. Approximately 400 kg of blast furnace slag is generated for every ton of pig iron smelted. Statistics show that in 2022, my country's pig iron production reached 869 million tons, equivalent to approximately 135 million tons of blast furnace slag.
[0003] The traditional method for treating blast furnace slag is water quenching, but this method has many drawbacks, such as high water consumption, wasting a lot of fresh water; the heat is not utilized and is wasted; the process generates a lot of sulfides that pollute the environment; reuse requires drying, which wastes a lot of energy; and the treated blast furnace slag is mainly used for roadbeds and backfill materials, with very low added value.
[0004] Dry slag treatment technology overcomes the various drawbacks of water quenching, eliminating the need for water resources, preventing the emission of harmful gases, and efficiently utilizing the waste heat of blast furnace slag. In recent years, this method has gradually become a primary research focus for blast furnace slag treatment by researchers and enterprises. Air quenching is considered the dry granulation process with the lowest slag discharge temperature (100℃) and the best waste heat recovery efficiency. Nippon Steel, Kawasaki Steel, and Sumitomo Metal Industries in Japan have jointly conducted experiments on air quenching granulation. This method has a large processing capacity, and the treated slag can be used as an active admixture in cement production. However, it suffers from drawbacks such as large equipment size, high air volume, and high energy consumption, requiring a long payback period. Currently, the use of air quenching combined with water quenching in steel plants significantly limits the subsequent utilization of slag products and results in a waste of secondary resources.
[0005] Due to its inherent compositional characteristics, blast furnace slag can inhibit the crystallization of various compounds under extreme high and low temperatures, while simultaneously converting thermal energy into chemical energy for preservation. The higher the amorphous content, the stronger its activity. This latent activity, upon encountering activators such as water, can generate materials with hydraulic cementitious properties, making it a high-quality raw material for cement production. To increase the substitution rate of granulated blast furnace slag as an active admixture in cement, it is necessary to maximize its glass content. Existing technologies include similar literature on blast furnace slag treatment, such as CN110342884A, entitled "A Method for Preparing Concrete Using Gas-Quenched Metallurgical Slag Microspheres as Aggregate," which uses blast furnace slag as a conditioning agent to prepare concrete with performance superior to ordinary concrete. CN102531425A, entitled "A Composite Admixture of Gas-Quenched Steel Slag and Blast Furnace Slag and Its Preparation Method," also uses a method of mixing steel slag and blast furnace slag to prepare cement admixtures, thereby improving cement strength performance. However, steel slag contains a large amount of free calcium oxide, which can cause expansion and cracking when used as a concrete admixture, leading to poor stability and other drawbacks that cannot be ignored. Although existing technologies have studied the utilization of blast furnace slag, it is only used in small quantities as a conditioning agent, and the thermal energy of blast furnace slag itself is not maximized. The added value of its utilization still needs to be further improved. Summary of the Invention
[0006] To address the shortcomings of existing technologies, the present invention aims to provide a method for enhanced cooling and granulation of blast furnace slag. This method involves gas-solid two-phase flow mixing and enhanced crushing, combined with cold core coating to enhance cooling and granulation of the blast furnace slag. It fully utilizes the waste heat of the blast furnace slag to crush and granulate the slag, obtaining amorphous slag beads. This significantly improves the bead formation rate and amorphous content of the amorphous slag beads, solving the technical bottlenecks in product quality control and efficient utilization of high-temperature waste heat during the blast furnace slag cooling and granulation process. The high glass content of the prepared amorphous slag beads can effectively increase the proportion of cement raw materials that can be replaced, improve cement performance, and enhance cement strength, thereby saving on the cost of cement clinker raw materials, improving socio-economic benefits, and significantly increasing the added value of blast furnace slag utilization while reducing environmental and resource harm—a truly multifaceted benefit. Meanwhile, hollow glass beads obtained by screening industrial solid waste fly ash or amorphous slag beads of blast furnace slag are used as cooling media (i.e., the following solid cold material) to form a "cold core hot slag" structure with the high-temperature liquid slag. This not only effectively enhances the crushing and granulation degree of the liquid slag, but also makes efficient use of the waste heat of the liquid slag. At the same time, amorphous slag beads of blast furnace slag can be used as active admixtures for cement.
[0007] The granulation process of molten slag in this invention mainly consists of three stages: primary crushing, secondary crushing, and solidification. First, the molten slag is subjected to high-pressure airflow, which initially forms a disturbance wave. As the high-speed airflow continues to act on the molten slag, the amplitude of the disturbance wave increases. Upon reaching a critical value, the disturbance wave breaks into film-like or cylindrical liquid filaments. This process is mainly related to the injection process parameters and the gas-liquid physicochemical properties (such as surface tension), constituting the primary crushing of the molten slag. To obtain slag beads with smaller and more uniform particle size, the molten slag must undergo secondary crushing as much as possible. This is achieved by mixing small-diameter solid cold material with high-pressure air to form a gas-solid two-phase flow that is then injected onto the molten slag. This enhances the granulation injection kinetic energy, fully utilizes the residual heat of the molten slag to ensure complete granulation, strengthens the crushing and granulation effect of the molten slag, and prepares small-diameter amorphous slag beads with uniform particle size. This effectively enhances the cooling degree of the slag beads and increases the glass content.
[0008] Blast furnace slag with high basicity exhibits "short slag" characteristics, with viscosity showing good fluidity as temperature increases. At high temperatures, the viscosity of molten slag is low, which is beneficial for granulation and fragmentation. However, at lower temperatures, the slag solidifies rapidly, making it impossible to inject molten slag. Conversely, blast furnace slag with low basicity exhibits "long slag" characteristics. At high temperatures, the molten slag has good fluidity, and its viscosity changes slowly as temperature decreases. As the temperature decreases, the molten slag is less prone to interionic movement, which is conducive to the formation of a glassy phase. However, if the basicity is too low, the strong interionic bonding can easily lead to the formation of fibers. Multiple experiments have shown that, overall, the method of this invention is suitable for blast furnace slag with a basicity of 1.0–1.3. It can ensure a high granulation rate and uniform slag bead size, while significantly increasing the glass content in amorphous slag beads, thus fully enhancing the added value of blast furnace slag utilization.
[0009] The objective of this invention is achieved through the following technical solution.
[0010] A type of amorphous blast furnace slag bead has a core-shell structure. The core is a solid cold material, and the shell is a slag shell formed by the surface tension of the molten blast furnace slag during the gas-solid two-phase flow injection granulation process under the control of the Weber number. The gas-solid two-phase flow is composed of a mixture of high-pressure gas and solid cold material.
[0011] A method for enhancing the cooling and granulation of blast furnace slag includes the following steps:
[0012] S1. Heat blast furnace slag with basicity of 1.0 to 1.3 (binary basicity) to 1500 to 1600°C and keep it at that temperature for 0.5 to 1 hour to make the blast furnace slag reach a flowable molten state to obtain liquid molten slag;
[0013] In S1, blast furnace slag with an alkalinity of 1.0 to 1.3 is heated to 1500 to 1600°C and kept at that temperature.
[0014] S2. Pour the molten slag into the inlet of the slag trough, and use a Laval nozzle to spray the molten slag flowing vertically downward at the outlet of the slag trough to obtain amorphous slag beads of blast furnace slag. The Laval nozzle sprays a gas-solid two-phase flow composed of high-pressure gas and solid cold material, which is used to break and granulate the molten slag while coating the solid cold material in the molten slag to form a "cold core hot slag" structure.
[0015] In S2, the flow velocity of the molten slag flowing downward from the outlet of the slag trough is 0.7 to 1 kg / s.
[0016] In S2, the orifice diameter of the Laval nozzle is 2-3 mm.
[0017] In S2, the diameter of the slag trough is 8-10 mm.
[0018] In S2, the Laval nozzle is connected to an air compressor via a pipeline, and a feeding funnel loaded with solid cold material is fixed on the pipeline. The outlet of the feeding funnel is connected to the pipeline, and the feeding rate of solid cold material supplied to the pipeline by the outlet of the feeding funnel is 50-80 g / s, preferably 60-80 g / s, and even more preferably 70-80 g / s.
[0019] In the above technical solution, the Laval nozzle is positioned directly below the outlet of the slag trough, wherein the nozzle cross-section and the slag trough outlet cross-section are on a straight line.
[0020] In the above technical solution, the air compressor is used to blow high-pressure air at 0.15 to 0.3 MPa.
[0021] In the above technical solution, the solid cold material is hollow glass beads with a particle size of 0.045-0.2 mm or amorphous blast furnace slag beads with a particle size of 0.075-1.0 mm obtained by screening fly ash (industrial solid waste used as cement admixture).
[0022] The beneficial effects of this invention are as follows:
[0023] 1. The blast furnace slag amorphous beads prepared by this invention have a high amorphous phase content and a high granulation rate, which can enable the cement replacement in cement active admixtures to reach 30-70%, effectively increasing the cement replacement and reducing CO2 emissions during cement production. The prepared mixed cement mortar has a 7-day compressive strength of over 49 MPa and a 28-day compressive strength of over 72 MPa. The performance of the mixed cement is superior to that of ordinary cement.
[0024] 2. The method for enhanced cooling and granulation of blast furnace slag of the present invention utilizes high-pressure gas-solid two-phase flow mixing to enhance the crushing, granulation, and cooling of blast furnace slag, which has the following advantages:
[0025] 2-1. The waste heat of blast furnace slag is fully utilized to keep the blast furnace slag in a suitable molten state for crushing. The high-pressure gas-solid two-phase flow is used to strengthen the crushing of the high-temperature molten liquid slag flow. The granulated slag beads are cooled from both the outside and the inside, which improves the granulation rate of blast furnace slag, effectively reduces the particle size of granulated slag beads, and increases the glass content of slag beads.
[0026] 2-2, The synergistic cooling method of using high-pressure gas-solid two-phase flow to enhance injection while simultaneously coating the slag beads with solid cold material as a cold nucleating agent can significantly accelerate the heat exchange rate of the slag beads, reduce the heat carried by the slag beads themselves, accelerate their own cooling and solidification rate, thereby effectively inhibiting the precipitation of crystalline phases inside the slag beads, significantly improving the potential activity of the slag beads, increasing the added value of blast furnace slag utilization, and reducing pollution and waste to the environment and resources. Attached Figure Description
[0027] Figure 1 A schematic diagram of the equipment used to achieve enhanced cooling and granulation of blast furnace slag;
[0028] Figure 2 The images are of amorphous blast furnace slag beads, where (a) is the amorphous blast furnace slag beads obtained in Example 1, (b) is the amorphous blast furnace slag beads obtained in Example 2, (c) is the amorphous blast furnace slag beads obtained in Example 3, and (d) is the amorphous blast furnace slag beads obtained in Example 4.
[0029] Figure 3 Microscopic images of amorphous slag beads of different particle sizes in blast furnace slag from Example 1. Detailed Implementation
[0030] The technical solution of the present invention will be further described below with reference to specific embodiments.
[0031] In the following examples, the blast furnace slag is produced from the blast furnace slag produced during the process of producing molten iron in the blast furnace of Tangshan Iron and Steel Plant.
[0032] Amorphous slag beads of blast furnace slag are products of molten silicate as the main component, which are rapidly cooled and granulated. Because the extremely cooling process does not meet the conditions for the formation of internal crystal phases in blast furnace slag, granulated slag beads containing a large amount of glass can be formed. They have good hydraulic cementitious properties and are high-quality raw materials for cement admixtures.
[0033] Examples 1-2
[0034] A method for enhancing the cooling and granulation of blast furnace slag includes the following steps:
[0035] S1. In a heating furnace, blast furnace slag with an basicity of 1.2 is heated to 1600℃ and kept at that temperature for 0.5h to make the blast furnace slag reach a flowable molten state and obtain liquid molten slag;
[0036] S2. The electric motor drives the heating furnace to rotate slowly, pouring molten slag from the furnace outlet to the slag trough inlet (the slag trough diameter is 10mm), so that the flow velocity of the molten slag flowing downwards at the slag trough outlet is 0.7kg / s. A Laval nozzle with a 3mm orifice is positioned directly below the slag trough outlet, with the nozzle cross-section aligned with the slag trough outlet cross-section. The Laval nozzle is used to spray the molten slag flowing vertically downwards at the slag trough outlet, producing amorphous slag beads. The Laval nozzle sprays a gas-solid two-phase flow consisting of a high-pressure gas and solid cold material, which is used to break up and granulate the molten slag while simultaneously encapsulating the solid cold material within the molten slag, forming a "cold core, hot slag" structure. The solid cold material has a particle size of 0.15 mm and is amorphous blast furnace slag beads (in the examples, the solid cold material is obtained by the enhanced cooling granulation method of the present invention, and the solid cold material used to obtain amorphous blast furnace slag beads for the first time in the enhanced cooling granulation method of the present invention is hollow glass beads with a particle size of 0.1 mm obtained by sieving from fly ash). The amorphous blast furnace slag beads obtained by the enhanced cooling granulation method of blast furnace slag in Examples 1 and 2 are as follows. Figure 2 As shown in (a) and (b), the microstructure of amorphous slag beads obtained by the enhanced cooling granulation method of blast furnace slag in Example 1 is as follows. Figure 3 As shown.
[0037] The gas-solid two-phase flow is achieved as follows: A Laval nozzle is connected to an air compressor via a pipeline, and the air compressor is used to blow high-pressure air at 0.2 MPa. A feeding funnel loaded with solid cold material is fixed on the pipeline, and the outlet of the feeding funnel is connected to the pipeline. The amount of solid cold material supplied to the pipeline from the outlet of the feeding funnel is shown in Table 1.
[0038] Table 1
[0039] Example The rate at which solid cold material is supplied from the outlet of the feeding funnel into the pipeline (unit: g / s). Example 1 80 Example 2 50
[0040] Example 3
[0041] A method for enhancing the cooling and granulation of blast furnace slag is basically the same as in Examples 1 and 2, the only difference being that in this example, the feeding funnel does not supply solid cold material to the pipeline, and the Laval nozzle only sprays gas, resulting in amorphous slag beads. Figure 2 As shown in (c).
[0042] Example 4
[0043] A method for enhancing the cooling and granulation of blast furnace slag is basically the same as that in Example 1, except that the basicity of the blast furnace slag in this example is 0.9.
[0044] The amorphous slag beads obtained in Examples 1-4 were tested:
[0045] Regarding the amorphous blast furnace slag beads prepared in Example 1: the particle size of the collected amorphous blast furnace slag beads was all less than 5 mm, and the bead formation rate was 73.33%. The glass content of the amorphous blast furnace slag beads was determined to be 95.79% according to GB / T18046-2017. According to GB / T18046-2017, the amorphous blast furnace slag beads were mixed with an equal mass of P.O42.5 ordinary Portland cement (reference cement). The resulting mixed cement mortar exhibited superior performance compared to the reference cement (e.g., compressive strength, durability). The compressive strength of the mixed cement mortar was tested at 7 days and 28 days according to the GB / T17671-2021 cement mortar strength method. Calculations showed that the 7-day compressive strength of the mixed cement mortar reached 57 MPa, and the 28-day compressive strength reached 85 MPa.
[0046] Regarding the amorphous blast furnace slag beads prepared in Example 1: the particle size of the collected amorphous blast furnace slag beads was all less than 5 mm, and the bead formation rate was 73.33%. The glass content of the amorphous blast furnace slag beads was determined to be 95.79% according to GB / T18046-2017. According to GB / T18046-2017, the amorphous blast furnace slag beads were mixed with P.O42.5 ordinary Portland cement (reference cement) at a mass ratio of 35:65. The resulting mixed cement mortar exhibited superior performance compared to the reference cement (e.g., compressive strength, durability). The compressive strength of the mixed cement mortar was tested at 7 days and 28 days according to GB / T17671-2021, and the calculated activity index of the 7-day compressive strength of the mixed cement mortar reached 49.4 MPa, while the activity index of the 28-day compressive strength reached 72.5 MPa.
[0047] Regarding the amorphous blast furnace slag beads prepared in Example 2: the particle size of the collected amorphous blast furnace slag beads was all less than 5 mm, and the bead formation rate was 67.76%. The glass content of the amorphous blast furnace slag beads was determined to be 94.67% according to GB / T18046-2017. According to GB / T18046-2017, the amorphous blast furnace slag beads were mixed with an equal mass of P.O42.5 ordinary Portland cement (reference cement). The resulting mixed cement mortar exhibited superior performance compared to the reference cement (e.g., compressive strength, durability). The compressive strength of the mixed cement mortar was tested at 7 days and 28 days according to the GB / T17671-2021 cement mortar strength method. Calculations showed that the 7-day compressive strength of the mixed cement mortar reached 53.2 MPa, and the 28-day compressive strength reached 82.5 MPa.
[0048] Regarding the amorphous blast furnace slag beads prepared in Example 3: the particle size of the collected amorphous blast furnace slag beads was all less than 5 mm, and the bead formation rate was 65.66%. The glass content of the amorphous blast furnace slag beads was determined to be 85.50% according to GB / T18046-2017. According to GB / T18046-2017, the amorphous blast furnace slag beads were mixed with an equal mass of P.O42.5 ordinary Portland cement (reference cement). The resulting mixed cement mortar exhibited superior performance compared to the reference cement (e.g., compressive strength, durability). The compressive strength of the mixed cement mortar was tested at 7 days and 28 days according to the GB / T17671-2021 cement mortar strength method. Calculations showed that the 7-day compressive strength of the mixed cement mortar reached 51.3 MPa, and the 28-day compressive strength reached 75 MPa.
[0049] Regarding the amorphous blast furnace slag beads prepared in Example 4: the particle size of the collected amorphous blast furnace slag beads was all less than 5 mm, and the bead formation rate was 40.33%. The glass content of the amorphous blast furnace slag beads, determined according to GB / T18046-2017, was 65.79%, which does not meet the quality requirement of >70% glass content for use as a substitute for slag cement. According to GB / T18046-2017, the amorphous blast furnace slag beads were mixed with an equal mass of P.O42.5 ordinary Portland cement (reference cement). The compressive strength of the mixed cement mortar was tested at 7 days and 28 days according to the cement mortar strength method in GB / T17671-2021. The compressive strength of the prepared mixed cement mortar was lower than that of the reference cement. The calculated 7-day compressive strength of the mixed cement mortar was 31.5 MPa, and the 28-day compressive strength was 45 MPa.
[0050] Smaller particle size of amorphous blast furnace slag beads facilitates internal heat exchange, optimizes waste heat utilization, and accelerates cooling, thus improving slag bead quality control. In summary, utilizing a gas-solid two-phase flow for combined internal and external intensified crushing and cooling of molten slag can effectively enhance cooling intensity, strengthen internal and external heat exchange within the beads, increase glass content in granulated beads, and improve the activity and substitution capacity of amorphous blast furnace slag beads as cement admixtures, thereby significantly improving the utilization quality of amorphous blast furnace slag beads.
[0051] When the solid cold material is amorphous slag beads of blast furnace slag, it forms a "cold core hot slag" structure with the liquid molten slag. This not only effectively enhances the crushing and granulation of blast furnace slag, but also makes efficient use of the waste heat of blast furnace slag. At the same time, the granulation medium and the granulated material are of the same type, which can avoid other substances from having an adverse effect on the subsequent utilization of blast furnace slag.
[0052] Example 6
[0053] The equipment for implementing the method of enhanced cooling and granulation of blast furnace slag in Example 3 is based on the gas quenching device according to Publication No. CN216688192U. The equipment for implementing the methods of enhanced cooling and granulation of blast furnace slag in Examples 1-2 and Example 4 can be of various types, for example, using... Figure 1 The device shown ( Figure 1 To install a feeding funnel on the pipeline in the air quenching device (publication number CN216688192U), Figure 1 The equipment shown includes: a heating furnace and a slag flow channel. Figure 1 The furnace includes a chute, an air compressor, a Laval nozzle, and a slag cooler. The heating furnace is an electric arc furnace used for loading blast furnace slag. The heating furnace has a charging port and a discharging port. Figure 1 The furnace has a slag outlet and is equipped with graphite electrodes for heating. Thermocouples are also installed inside the furnace to measure the internal temperature. A jacket, connected to water-cooling pipes, is installed on the side wall of the furnace for cooling.
[0054] Slag trough: Liquid molten slag is poured from the outlet of the heating furnace onto the slag trough, which can maintain the stability and shape of the liquid molten slag; the outlet of the slag trough is a graphite sleeve, which can maintain the shape of the liquid molten slag during injection.
[0055] The feeding funnel is used to supply cold solid material during the granulation process;
[0056] The air compressor is used to provide the output of high-pressure air for the granulation process; Laval nozzles ( Figure 1 The gas quenching nozzle is used to spray and granulate liquid slag;
[0057] The slag cooler is used to collect amorphous slag beads from blast furnace slag and to recover and utilize the heat from the amorphous slag beads. Cold water is introduced into the slag cooler.
[0058] A condenser is used to accelerate the cooling of amorphous slag beads from blast furnace slag.
[0059] The present invention has been described above by way of example. It should be noted that any simple modifications, alterations or other equivalent substitutions that can be made by those skilled in the art without creative effort without departing from the core of the present invention fall within the protection scope of the present invention.
Claims
1. A method for enhancing the cooling and granulation of blast furnace slag, characterized in that, Includes the following steps: S1. Heat blast furnace slag with an alkalinity of 1.0~1.3 to 1500~1600℃ and keep it at that temperature for 0.5~1h to make the blast furnace slag reach a flowable molten state to obtain liquid molten slag; S2. The molten slag is poured into the inlet of the slag trough, and the molten slag flowing vertically downwards from the outlet of the slag trough is sprayed using a Laval nozzle to obtain amorphous slag beads of blast furnace slag. The Laval nozzle sprays a gas-solid two-phase flow consisting of a mixture of high-pressure gas and solid cold material, which is used to break and granulate the molten slag while coating the solid cold material in the molten slag to form a "cold core hot slag" structure. The solid cold material is hollow glass beads with a particle size of 0.045~0.2mm obtained by screening fly ash or amorphous slag beads of blast furnace slag with a particle size of 0.075~1.0mm. The Laval nozzle is connected to an air compressor through a pipeline, and a feeding funnel loaded with solid cold material is fixed on the pipeline. The outlet of the feeding funnel is connected to the pipeline, and the feeding rate of solid cold material supplied to the pipeline from the outlet of the feeding funnel is 50~80 g / s.
2. The method according to claim 1, characterized in that, The amorphous slag beads of blast furnace slag have a core-shell structure. The core is a solid cold material, and the shell is a slag shell formed by the surface tension of the molten blast furnace slag during the gas-solid two-phase flow injection granulation process under the control of the Weber number. The gas-solid two-phase flow is composed of a mixture of high-pressure gas and solid cold material.
3. The method according to claim 1, characterized in that, In S2, the orifice diameter of the Laval nozzle is 2~3mm.
4. The method according to claim 1, characterized in that, In S2, the diameter of the slag trough is 8~10mm.
5. The method according to claim 1, characterized in that, The Laval nozzle is positioned directly below the outlet of the slag trough, with the nozzle cross-section and the slag trough outlet cross-section aligned in a straight line.
6. The method according to claim 1, characterized in that, The air compressor is used to blow high-pressure air at 0.15~0.3MPa.
7. The method according to claim 3, characterized in that, In S2, the flow velocity of the molten slag flowing downward from the outlet of the slag trough is 0.7~1kg / s.
Citation Information
Patent Citations
Composite doping material of air-quenched steel slag and blast furnace slag and preparation method of composite doping material
CN102531425A
Preparation method of concrete which adopts gas quenching metallurgical slag microbeads as aggregate
CN110342884A
Heat recovery method for blast furnace slag
CN102851416A
Slag quenching and granulating equipment
CN114807463A